INNOCULANT TECHNOLOGY IN POPULUS DELTOIDES RHIZOSPHERE FOR EFFECTIVE BIOREMEDIATION OF POLYAROMATIC HYDROCARBONS (PAHS) IN CONTAMINATED SOIL, NORTHERN INDIA - Bisht, Sandeep; Kumar, Vivek; Kumar, Manoj; Sharma, Shivesh (Emirates Journal of Food and Agriculture, 2014)
Four bacterial strains viz. Kurthia sp. SBA4, Micrococcus varians SBA8, Deinococcus radiodurans SBA6 and Bacillus circulans SBA12 identified as Polyaromatic hydrocarbons (PAH) degrader, isolated form the rhizospheric soil of Populus deltoides growing in non-contaminated sites of Uttarakhand Himalyan region, India. Out of these four isolates, M. varians SBA8 degraded appreciable amount of PAH along with some plant growth promoting properties viz. indole acetic acid (IAA) 19 µg ml-1, phosphate solubilization 1.8 µg ml-1 produced siderophore and possessed ACC deaminase activity. Along with these traits, M. varians SBA8 also exhibited biocontrol activities against phytopathogenic fungi Rhizoctonia solanii, Macrophomina phaseolina and Fusarium oxysporum with 50, 43.3 and 34.6 percent growth inhibition (PGI). Moreover, mycelial deformities were also observed in the test fungal spp. The M. varians SBA8 proved to be competent rhizobacteria in rhizosphere niche in treatments T1 (Sterile soil + plant cuttings + bacterization) and T2 (sterile soil + anthracene + plant cuttings + bacterization). Rhizoremediation potential of M. varians SBA8 was also determined in PAH amended soil model system. Significant enhancement in shoot, root length, root and shoot biomass including stem girth of P. deltoides with respect to control was recorded and concurrently the bacterium degraded 43.6 % of PAH as determined by HPLC analysis in soil model system after 120 days of inoculation. Multipurpose inoculant was also formulated using M. varians SBA8 strain immobilized in different lignocellulosic waste material used as carriers. Rock phosphate, cocoa peat and wheat bran based bioinoculant were found suitable for rhizoremediation of PAH.